2007
DOI: 10.1210/en.2006-0752
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Cold Thyroid Nodules

Abstract: Cold thyroid nodules (CTNs) represent a frequent endocrine disorder accounting for up to 85% of thyroid nodules in a population living in an iodine-deficient area. Benign CTNs need to be distinguished from thyroid cancer, which is relatively rare. The molecular etiology of benign CTNs is unresolved. To obtain novel insights into their pathogenesis, protein expression profiling was performed in a series of 27 solitary CTNs (10 follicular adenoma and 20 adenomatous nodules) and surrounding normal thyroid tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
2
32
0
1
Order By: Relevance
“…The molecular pathogenesis of benign CTNs is unknown. We recently performed a proteomic study of benign CTNs, where we found evidence for increased expression of APP, APP-binding protein and APP-p3-component in CTNs (Krause et al 2007b). Since CTNs exhibit certain signs of dedifferentiation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular pathogenesis of benign CTNs is unknown. We recently performed a proteomic study of benign CTNs, where we found evidence for increased expression of APP, APP-binding protein and APP-p3-component in CTNs (Krause et al 2007b). Since CTNs exhibit certain signs of dedifferentiation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent proteomic study, we have identified an increased expression of APP, the amyloid precursor-binding protein 1 (APPBP1) and the APP-p-component in benign cold thyroid nodules (CTNs) compared with normal thyroid tissue (Krause et al 2007b). The molecular aetiology of CTNs is unknown and at present it is unclear, if the CTN represents a truly benign thyroid neoplasm or a lesion with the potential for further dedifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Fifty micrograms of protein, adapted to an equal thyroglobulin amount, was subjected to 10% SDS-PAGE, transferred to nitrocellulose membranes, and probed with anti-TCTP antibody (Abcam, Cambridge, UK). Rabbit IgG conjugated with peroxidase was used as secondary antibody (1.0000; Cell Signaling, Charlottesville, VA) and was visualized by enhanced chemiluminescence (Pierce, Milwaukee, WI).…”
Section: Immunoblottingmentioning
confidence: 99%
“…18 The following primary antibodies were used: antiphospho-Chk2 (Thr68), anti-phospho-H2AX (Ser139) (both from Cell Signaling Technology), anti-I2 protein phosphatase 2A (PP2A), and anti-DJ-1 (both from Abcam). For controls, tissues from colon carcinomas (for ␥-H2AX and pChk2), Graves' disease (for DJ-1), and breast carcinomas (for I2PP2A) were used.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation